Hvad er litteratursociologi? Historisk rids og aktuelle debatter - Tanderup Linkis, Sara; Gormsen Schmidt, Johanne (Passage - Tidsskrift for litteratur og kritik, 2023)
Since its heyday in the 1960 and 70s, the sociology of literature has been declared dead and gone, yet research related to the field also seems to be reemerging in the first decades of the 21st century. Research relating to the field is scattered across other disciplines, such as literary studies, media studies and cultural studies; indeed, sociology of literature is “everywhere and nowhere”, as James English put it in 2010. But where is it now? Departing from recent perspectives on the sociology of literature by e.g. English, Wendy Griswold, and Johan Svedjedal, the article traces a brief history of the field and discusses future directions for the sociology of literature relating to current trends in literary studies and studies in book culture – including a recent attention towards uses of literature and methodological developments linked to digital methods as well as media-specific analysis and intermedial approaches to books and literature.